2019
DOI: 10.1111/ijpp.12524
|View full text |Cite
|
Sign up to set email alerts
|

Self-rated health and medicine beliefs among older hospital outpatients in Hong Kong

Abstract: Objectives (1) To identify any demographic characteristics, which predict medicines adherence by reporting Necessity‐Concern Differential (NCD) and Self‐Reported Health (SRH) scores among Hong Kong hospital outpatients. (ii) To investigate any association between SRH and NCD in this cultural group. Methods A total of 709 outpatients completed a questionnaire consisting demographic information, SRH and Belief about Medicines Questionnaire. Findings were analysed statistically. Key findings Descriptive statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 26 publications
(50 reference statements)
1
6
0
Order By: Relevance
“…This strengthened our proposal that SRH has a potential role in prompt detection of medication non‐believers and, thus, non‐adherers. [ 5 ]…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This strengthened our proposal that SRH has a potential role in prompt detection of medication non‐believers and, thus, non‐adherers. [ 5 ]…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our recent study in a Hong Kong regional teaching hospital demonstrated middle‐aged and older pharmacy outpatients’ subjective health status significantly predicted their medicine specific beliefs reporting. [ 5 ] However, general beliefs were not investigated in that study. The researchers also suggested that this association may pave the way for early screening of potential medicine non‐believers and, thus, non‐adherers.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations